Effectiveness of a Novel Qigong Meditative Movement Practice for Impaired Health in Flight Attendants Exposed to Second-Hand Cigarette Smoke - Payne, Peter; Fiering, Steven; Leiter, James C.; Zava, David T.; Crane-Godreau, Mardi A. (Frontiers in Human Neuroscience, 2017)
This single-arm non-randomized pilot study explores an intervention to improve the health of flight attendants exposed to second-hand cigarette smoke prior to the smoking ban on commercial airlines. This group exhibits an unusual pattern of long-term pulmonary dysfunction. We report on Phase I of a two-phase clinical trial; the second Phase will be a randomized controlled trial testing digital delivery of the intervention. Subjects were recruited in the Northeastern US; testing and intervention were administered in 4 major cities. The intervention involved 12 hours of training in Meditative Movement practices. Based on recent research on the effects of nicotine on fear learning, and the influence of the autonomic nervous system on immune function, our hypothesis was that this training would improve autonomic function and thus benefit a range of health measures. Primary outcomes were the six-minute walk test and blood levels of C-reactive protein. Pulmonary, cardiovascular, autonomic and affective measures were also taken. Fourteen participants completed the training and post-testing. There was a 53% decrease in high sensitivity C-Reactive Protein (p<=0.05), a 7% reduction in systolic blood pressure (p<=0.05), a 13% increase in the 6-minute walk test (p<=0.005), and significant positive changes in several other outcomes. These results tend to confirm the hypothesized benefits of MM training for this population, and indicate that autonomic function may be important in the etiology and treatment of their symptoms. No adverse effects were reported. This trial is registered at ClinicalTrials.gov (https://clinicaltrials.gov/ct2/show/NCT02612389/), and is supported by a grant from the Flight Attendant Medical Research Institute (FAMRI).